Abrupt climate change and its influences on hominin evolution during the early Pleistocene in the Turkana Basin, Kenya. (1st October 2020) - Lupien, Rachel L.; Russell, James M.; Grove, Matt; Beck, Catherine C.; Feibel, Craig S.; Cohen, Andrew S.
Abstract: Rapid climate variability has been hypothesized to play an important role in hominin evolution, yet our knowledge of Plio-Pleistocene climate change on short timescales is poor. Here, we developed centennial-scale reconstructions of precipitation from leaf wax biomarker hydrogen isotope ratios (δDwax ) using lacustrine sediment from West Turkana, Kenya. We analyzed two time intervals (∼1.72 and ∼1.60 Ma) with different orbital configurations (0.043 and 0.025 eccentricity, respectively) to examine the influence of seasonal insolation forcing on high-frequency climate variability and the rates of climate transitions. Our data indicate that under low summer insolation, which should induce high latitude glaciation and tropical African aridity, millennial-scale climate variability was stronger. This suggests that hominins may have been forced to contend with increased climate variability during already extreme environmental conditions. Additionally, we observe a rapid shift from arid to humid conditions occurring in less than 200 years under high-amplitude precessional-scale insolation change. The rate of this transition is similar to that observed in some proxy records of the onset of the African Humid Period, indicating high sensitivity to gradual insolation forcing in the Turkana Basin. Such abrupt climate changes could induce evolutionary selection for generalist behavioral traits in hominins. Highlights: High-resolution Turkana δDwax was measured in two early Pleistocene intervals. High-frequency climate variability was strongest during low insolation times. An abrupt, large-amplitude climate transition occurred during increasing insolation. These changes may have influenced early human evolution and Acheulean innovation.